Vorolanib, sunitinib, and axitinib: A comparative study of vascular endothelial growth factor receptor inhibitors and their anti-angiogenic effects - Bakri, Sophie J.; Lynch, Jeff; Howard-Sparks, Michelle; Saint-Juste, Stephan; Saim, Said (PLOS ONE, 2024)
Purpose Pathological angiogenesis and vascular instability are observed in diabetic retinopathy (DR), diabetic macular edema (DME), and wet age-related macular degeneration (wAMD). Many receptor tyrosine kinases (RTKs) including vascular endothelial growth factor receptors (VEGFRs) contribute to angiogenesis, whereas the RTK TIE2 is important for vascular stability. Pan-VEGFR tyrosine kinase inhibitors (TKIs) such as vorolanib, sunitinib, and axitinib are of therapeutic interest over current antibody treatments that target only one or two ligands. This study compared the anti-angiogenic potential of these TKIs. Methods A kinase HotSpot™ assay was conducted to identify TKIs inhibiting RTKs associated with angiogenesis and vascular stability. Half-maximal inhibitory concentration (IC50) for VEGFRs and TIE2 was determined for each TKI. In vitro angiogenesis inhibition was investigated using a human umbilical vein endothelial cell sprouting assay, and in vivo angiogenesis was studied using the chorioallantoic membrane assay. Melanin binding was assessed using a melanin-binding assay. Computer modeling was conducted to understand the TIE2-axitinib complex as well as interactions between vorolanib and VEGFRs. Results Vorolanib, sunitinib, and axitinib inhibited RTKs of interest in angiogenesis and exhibited pan-VEGFR inhibition. HotSpot™ assay and TIE2 IC50 values showed that only axitinib potently inhibited TIE2 (up to 89%). All three TKIs effectively inhibited angiogenesis in vitro. In vivo, TKIs were more effective at inhibiting VEGF-induced angiogenesis than the anti-VEGF antibody bevacizumab. Of the three TKIs, only sunitinib bound melanin. TKIs differ in their classification and binding to VEGFRs, which is important because type II inhibitors have greater selectivity than type I TKIs. Conclusions Vorolanib, sunitinib, and axitinib exhibited pan-VEGFR inhibition and inhibited RTKs associated with pathological angiogenesis. Of the three TKIs, only axitinib potently inhibited TIE2 which is an undesired trait as TIE2 is essential for vascular stability. The findings support the use of vorolanib for therapeutic inhibition of angiogenesis observed in DR, DME, and wAMD.